Correlation analysis of serum TSG-14 and CORS26 levels with diabetic retinopathy: Serum TSG-14 and CORS26 levels with diabetic retinopathy - Wang, Yuqing; Lin, Shuhua; Yuan, Li; Gao, Xiaojuan; Lin, Lingli; Li, Xiaoqing; Zhang, Zhaode (Journal of Medical Biochemistry, 2026)
Objective To investigate the relationship between serum Cartilage Oligomeric Matrix Protein Like 26 (CORS26), TNF-stimulated gene 14 (TSG-14), and diabetic retinopathy (DR). Methods 276 patients with type 2 diabetes mellitus (T2DM) who were admitted to our hospital between April 2023 and April 2025 participated in a single-center cross-sectional analysis. These patients were divided into a DR group (156 patients) and a non-DR group (120 patients) based on the diagnostic findings. A nonproliferative DR (NPDR) group comprising 98 individuals and a proliferative DR (PDR) group comprising 58 patients were divided from the DR group. The associations between the markers of glycolipid metabolism, TSG-14, and CORS26 were examined using the Pearson method. A logistic analysis was conducted to examine the variables influencing DR in individuals with type 2 diabetes. The diagnostic utility of serum TSG-14 and CORS26 for DR in T2DM patients was assessed using ROC curves. Results The overall information for the two patient groups was similar. While the level of HDL-C was lower than that of the non-DR group, the levels of serum TSG-14, CORS26, TC, TG, LDL-C, and HOMA-IR were higher in the DR group (all P<0.05). The PDR group’s serum levels of TSG-14 and CORS26 were higher than those of the NPDR group (both P<0.05). Serum TSG-14 and CORS26 had a negative connection with HDL-C and a positive correlation with TC, TG, LDL-C, and HOMA-IR (all P<0.001). In patients with type 2 diabetes, the logistic regression analysis revealed that the following risk factors were associated with the occurrence of DR: length of diabetes, TC, TG, LDL-C, HOMA-IR, TSG-14, and CORS26 (all P<0.05). Serum TSG-14 and CORS26 areas under the curve (AUCs) for diagnosing DR in patients with type 2 diabetes (T2DM) were 0.833, 0.832, and 0.918, respectively, according to the ROC curve. The AUC of the combined diagnosis was greater than that of TSG-14 or CORS26 alone (Z = 2.811, 2.827; P = 0.018, 0.015). Conclusion The levels of serum TSG-14 and CORS26 are closely related to the occurrence of DR in patients with T2DM. Combined detection has certain clinical value for diagnosing DR in patients with T2DM.